2018
DOI: 10.1017/s0272263117000407
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Vocabulary Acquisition Through Viewing L2 Television and Factors That Affect Learning

Abstract: Research has begun to demonstrate that L2 words can be learned incidentally through watching audio-visual materials. Although there are a large number of studies that have investigated incidental vocabulary learning through reading a single text, there are no studies that have explored incidental vocabulary learning through viewing a single full-length TV program. The present study fills this gap. Additionally, three word-related variables (frequency of occurrence, cognateness, word relevance) and one learner-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

48
317
6
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 259 publications
(383 citation statements)
references
References 54 publications
(116 reference statements)
48
317
6
12
Order By: Relevance
“…Previous research into vocabulary learning from audiovisual input explored a number of learner‐related and word‐related variables that might affect the learning gains from audiovisual input. For instance, several studies (e.g., Montero Perez et al, , ; Peters & Webb, ) have shown that learners’ prior vocabulary knowledge, often measured by means of a vocabulary levels test or vocabulary size test, is positively related to word learning. The more words a learner knows, the more words they will pick up while watching TV.…”
Section: Factors Affecting Vocabulary Learning From Audiovisual Inputmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research into vocabulary learning from audiovisual input explored a number of learner‐related and word‐related variables that might affect the learning gains from audiovisual input. For instance, several studies (e.g., Montero Perez et al, , ; Peters & Webb, ) have shown that learners’ prior vocabulary knowledge, often measured by means of a vocabulary levels test or vocabulary size test, is positively related to word learning. The more words a learner knows, the more words they will pick up while watching TV.…”
Section: Factors Affecting Vocabulary Learning From Audiovisual Inputmentioning
confidence: 99%
“…Researchers have also addressed the role of a number of word‐related variables in vocabulary learning through TV viewing. Frequency of occurrence has been found to affect word learning positively (Peters & Webb, ), although its effect seems to be smaller in longitudinal studies that investigated extensive viewing (Rodgers & Webb, ). In a recent study, Puimège and Peters () found that a word’s corpus frequency was positively correlated to word learning at the level of form recall.…”
Section: Factors Affecting Vocabulary Learning From Audiovisual Inputmentioning
confidence: 99%
See 3 more Smart Citations